Forest management in the XXI Century - Aguirre-Calderón, Oscar Alberto (Instituto de Ecología, A.C., 2015)
The sustainable forest management in the twenty-first century is a principle that ensures the production of several goods and services from forest ecosystems in a permanent and optimal manner, maintaining always the values of such ecosystems; it is a strategy for natural resources management, in which forestry activities are considered in the ecological, economic and social context, within a defined area or region, in a short and long term. The challenge of sustainable forest management is the stewardship and use of the forests and forest lands in a manner and with an intensity that they preserve their biological diversity, its productivity, its capacity for regeneration, its vitality and ability to achieve, in the present and in the future, the ecological, economic and social functions relevant to local, national and global level, without causing damage to other ecosystems. This paper reviews the evolution of the forest management concept and the new paradigms for its implementation, highlighting their features such as administrative process, its relations with the provision of environmental services, the role of the certification for the development of good forest management, the importance of the decision-making process, the challenges of sustainable forest management, and the research needed for its implementation with scientific bases. It also emphasizes the need to train human resources, creating and improving capabilities for the planning, execution and monitoring of forest management.